STRATEGIES FOR FUNCTIONAL COMPETENCY DEVELOPMENT OF NEWSPAPER JOURNALISTS IN THE CONVERGENCE - ตระกูลทัศน์เจริญ, ภูมิพัฒน์; กิจรัตน์ภร, เปรื่อง; สามารถ, ภาณุพงศ์; โพธิ์มณี, เกรียงไกร (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2019)
The objectives of this study were to examine the competency requirement in the journalistic work, development strategy in the journalistic work. Data collection from daily newspaper’s reporters including Thairath, Daily News, Khaosod, Komchadluek and Matichon in total 104 samples through questionnaires, and 40 publishing executives, journalism experts and reporters by in-depth interviews and brainstorm workshops. The study found that key competency were knowledge, for example; media literacy, news analysis, laws of mass media having the mean of 4.17, competency on skill such as reporter’s ability on storytelling, critical news writing having the mean of 4.15, attribute and attitude such as reporter’s enthusiasm and sociability having the mean of 4.13 competency on the use of information technology to follow the progress of technology and make quotation on the information sources having the mean of 4.15 and the competency on ethics and code of ethics of Journalism such as reporting without prejudice having the mean of 4.22. As for the important strategies for the journalist competency development were-Strategy on knowledge; Strategy on skills; Strategy on attribute and attitude; Strategy on information technology usage and Strategy on ethics and code of ethics of Journalism.